Analisis Kebijakan Ekonomi Pengembangan Pelabuhan di Provinsi Aceh - Mandasari, Mandasari; Kusumastanto, Tridoyo; Mulyati, Heti (Jurnal Ekonomi dan Pembangunan Indonesia, 2017)
Port development was becoming a major issue in promoting national and regional economic competitiveness. However, the development of public ports in Aceh province has not been significantly caused by low port economic activity. This research used Linear Programming, qualitative description, and Analytical Hierarchy Process method. The result showed the main economic policy of port development in Aceh Province was to developing economic growth centers in hinterland by developing sectors producing goods such as agriculture, forestry and fishery sector, mining and quarrying sector, and industrial sector. The another policy was strengthen connectivity port-hinterland logistics network by improving the quality connectivity infrastructure, enhancing cooperation between port operators with exporters and logistics service providers, and build the dry port.